A case report of a de Garengeot hernia in a nonagenarian veteran. (2017) - Taveras, Luis R.; Huerta, Sergio
Highlights: A hernia containing the vermiform appendix [de Garengeot hernia (DGH)] is an exceedingly rare event. Most cases of DGH are made during inguinal exploration. In the present report, we discuss a patient who underwent an operation which revealed a DGH with appendicitis. This case is unusual because it occurred in a nonagenarian male veteran patient. The unique aspect of this case is that it was performed in its entirety under local anesthetic. Abstract: Introduction: A hernia containing the vermiform appendix [de Garengeot hernia (DGH)] is an exceedingly rare event. Appendicitis occurring in this setting if further unusual. Most cases of DGH are made during inguinal exploration. In the present report, we discuss a patient who underwent an operation which revealed a DGH with appendicitis. Presentation of a case: A 94-year-old man with a past medical history significant for hypertension and Parkinson's disease was admitted to the hospital for the management of an event of CHF exacerbation. He developed acute onset of a painful right inguinal bulge. He had no prior hernia history. On physical exam, he had a 3-cm, tender, non-reducible right inguinal bulge without skin changes. Laboratory analyses were normal without leukocytosis. An acute abdominal series was obtained and demonstrated no obstruction. A groin exploration was performed under local anesthetic. An abscess was found associated with a femoral hernia containing the vermiform appendix. An appendectomy was performed through the hernia sac. The hernia was repaired via a McVay technique. At thirty days after his procedure, he had no complications and no signs of recurrence. Conclusion: Most cases of DGH are diagnosed intraoperatively. Limited work up might be sufficient for adequate management. Several surgical strategies are acceptable. Groin exploration, plus and minus an appendectomy, and tissue repair versus mesh placement are acceptable surgical strategies. Laparoscopic approach for the management of DGH has been reported.